Development of Interactive Learning Media Based on Google Sites In Physics Learning for Class XI - Ulil Kurnia; Ulfia Rahmi; Alwen Bentri; Ridwan (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop a valid, practical, and effective Google Sites-based interactive learning media for Grade XI Physics. The research employed the Research and Development (R&D) method, utilizing the 4D development model which consists of four phases: Define, Design, Develop, and Disseminate. The data sources included assessments from experts, educators, and students, which described the level of validity, practicality, and effectiveness of the developed media. The validity test results indicated that the Google Sites-based interactive learning media is suitable for implementation in the learning process according to experts. The responses from educators and students also demonstrated that the media is practical for use in learning. The effectiveness test results revealed that the developed interactive learning media is effective in improving student learning outcomes, with an N-Gain score of 0.76 for the knowledge aspect. Meanwhile, for the skills aspect, it was categorized as moderately effective with an N-Gain score of 0.73. Therefore, the Google Sites-based interactive learning media is valid, practical, and effective for use in the Physics learning process.